2009
DOI: 10.31165/nk.2009.21.32
|View full text |Cite
|
Sign up to set email alerts
|

Igorots in the Blogosphere: Claiming Spaces, Re-constructing Identities

Abstract: Indigenous peoples in the Philippines have rarely been covered by the mainstream media, despite comprising 20 percent of the country’s total population. Lacking access to the media due to various constraints, they have had limited opportunities to create content themselves. But the emergence of the Internet, particularly blogs, is now providing members of indigenous communities with the much-needed space for self-expression. More particularly, several indigenous groups in North Luzon, collectively known as Igo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The concept of translocal and transnational modes of cultural reproduction proposes a dynamic and continually evolving view and experience of the global world through transgression of boundaries between spaces of very different scale and type, as well as through the re-creation of local distinctions between those spaces (Freitag & Oppen, 2010, p. 6). It has been observed that migration has given Indigenous Peoples access to global exploration and connection, resulting in redefining their Indigenous image and identity through technology and social media (Botangen et al, 2017;Longboan, 2009). As Igorots continue to move and interact in different parts of the world, studies show that they work towards making meaning of their culture of origin in the new space they are in.…”
Section: Potential and Challenges Of The Ili Concept Of Organisingmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of translocal and transnational modes of cultural reproduction proposes a dynamic and continually evolving view and experience of the global world through transgression of boundaries between spaces of very different scale and type, as well as through the re-creation of local distinctions between those spaces (Freitag & Oppen, 2010, p. 6). It has been observed that migration has given Indigenous Peoples access to global exploration and connection, resulting in redefining their Indigenous image and identity through technology and social media (Botangen et al, 2017;Longboan, 2009). As Igorots continue to move and interact in different parts of the world, studies show that they work towards making meaning of their culture of origin in the new space they are in.…”
Section: Potential and Challenges Of The Ili Concept Of Organisingmentioning
confidence: 99%
“…For example, stories shared by Igorot immigrants in the book Two Homes for One Heart: Igorot Immigration Stories (Adonis, 2017) unravels the longing to re-create the Igorot ili overseas. Hence, Igorot community groups are organised under the umbrella of Igorot Global Organization (IGO) and BIBAK (Adonis, 2017;Longboan, 2009). These groups organise purposely to support one another and create an imagined Igorot ili space in their 'new home'.…”
Section: Potential and Challenges Of The Ili Concept Of Organisingmentioning
confidence: 99%